WHEN INCOME IS LIMITED, DOES WORKING AS WORSHIP STILL CREATE WELFARE: CAREER MOM IN PRIVATE SECTOR CASE - Dewi Insyirahti Salsabilla; Ali Muhtarom; Muhammad Shulthoni; Muhammad Fathrezza Imani (Branding: Jurnal Manajemen dan Bisnis, 2026)
The role of mothers is crucial in the global era, and their presence is the foundation of life. The knowledge that mothers play a role in all areas is believed to have an impact on the nation. Mothers not only spend their lives at home, but some also help by working in addition to taking care of the household. This study aims to provide an overview of the motivation of blessing and gratitude as the basis for work enthusiasm, considering the many costs not covered by a low basic salary, such as childcare costs. The method used is qualitative primary sources. It is hoped that this study will have a positive impact on stakeholders in the private and public sectors, allowing them to consider policies related to the economic welfare of career mothers by providing various facilities to support their improvement.